Performance optimisation of the combined single flash binary geothermal power plant - Dagdas, Ahmet (INDERSCIENCE ENTERPRISES LTD, 2011)
In this paper, the optimal operating conditions of a hypothetical combined single flash-binary geothermal power plant are investigated and performance analyses are performed based on Aydin-Germencik field in Turkey. The relationship between flashing pressure, turbine inlet pressure of the binary cycle and total heat transfer area of the heat exchanger are determined for maximum power output of the combined power plant. According to the results, the optimal flashing pressure of the flash cycle and the optimal inlet pressure of the working fluid to binary cycle's turbine were found to be 500 kPa and 3620 kPa, respectively. In these pressures, the total power output of the combined power plant and the total heat transfer area of the heat exchanger have been calculated as 23,065 kWe and 6924 m(2), respectively.
Keywords: geothermal; power plant; exergy; optimisation; Germencik; Turkey; Thermodynamics; Energy & Fuels